Review Artikel : PEMANFAATAN KULIT PISANG RAJA (Musa paradisiaca L.) DALAM FORMULASI SEDIAAN KOSMETIK - Olii, Audia Triani; Mursyid, Mumtihanah; Shinta, Fitriyah Maya (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Plantain peel contains flavonoid compounds that can be used as sunscreen. The purpose of this research is to optimize the preparation of plantain peel extract lotion (Musa paradisiaca L.). The use of Tween 80 and Span 80 in lotion preparations can form a stable in-water oil-type emulsion. The lotion formula is optimized then produces the optimal formula obtained on the use of Tween 80 (6.9%) and Span 80 (3.1%). The optimal formula has a pH of 5.78; viscosity of 20613.33 cPs; adhesion of 4.6 seconds; a spread of 6.23 cm/sec; and determination of an SPF value of 17.262. The optimal formula of the optimization method has insignificant differences. The stability test results of the optimum lotion formula show a stable formula result.